Connecting the use of Biofertilizers on Maize silage or Meadows with Progress in Milk Quality and Economy - Giorgio, Masoero; Riccardo, Ariotti; Giusto, Giovannetti; Enrico, Ercole; Alberto, Cugnetto; Marco, Nuti (Journal of Agronomy Research, 2021)
A systematic use of biofertilizers can improve both the quality of a farming system and the parameters of milk. Some issues related to biofertilization experiments on six farms in the Po Valley (NW Italy) involved in the production of milk from dairy cattle fed maize silage or grazed on hay produced from permanent meadows are reported in this paper. Biofertilized maize was found to lower the live stem pH by about 2.3%, and NIR spectroscopy foreshadowing major changes in the composition. Overall, the plant silage was improved in quantity (+10%) but also in quality, as shown by the delayed maturity stage of the leaves (crop maturity index -4%), the lower indigestible NDF content (-7%), and the higher digestible carbohydrates and protein in the whole plants. Such favorable feeding conditions, together with the improved palatability of the feed ration, boosted the nutrient values of the protein (+4.6%) and fat contents (+5.7%) in the milk. Moreover, the functional properties of the milk were ameliorated, as testified by the higher levels of vitamin A (+27%) and vitamin E (+25%) and the reduced levels of saturated fatty acids (-6%), especially myristic (-18%) and stearic (-32%) acids, while the unsaturated acids increased by 15%. As far as economy aspects are concerned, the biofertilization of maize for silage has led to consistent rewards pertaining to the marginal price of the milk, which in turn has led to a value chain increase of about 9%, because of the fields cultivation, but mainly of the cow transformation in milk quality issues. On another farm, intensive maize was substituted with permanent biofertilized meadows, over a greening path, and a + 17% value chain increase was obtained that already derived mainly from the best price for milk quality parameters. Such an evolutionary leap toward a new vision of sustainable agriculture for the environment and for animals, in which a better quality of products, animal welfare and company budget are combined with soil biofertilization, can be considered a bonanza.
Keywords: Biofertilizer; farming economy; fat; maize silage; meadow; milk; mycorrhizae; protein; unsaturated fatty acids; vitamin A; vitamin E.